VARIASI DAN APLIKASI AFIKS DALAM KALIMAT DAN TUTURAN BERBAHASA INGGRIS - Sari, Mezia Kemala (Menara Ilmu, 2017)
Affix is one of the necessary thing in language including English.  The aim of this research is to find out the varieties of affixes in English and the application into sentences or utterance which commonly occur in daily used. The purposes of this research are to classify affixes in English and attempt to explain about the affixation process and also the use in sentences.The method of research is descriptive qualitative. The data collected by using documentating technique taken from the document sources like dictionary, books and notes.The finding is there are 4 kinds of affixes in English: Preffix, Suffix, Interfix and Superfix or Suprafix.The result  shows that in daily spoken and written language used, the four kinds of affixes are commonly occured and it indicates that English also experience the affixation process in order to compose a new word from the based form and had been common to be used in daily utterance in everyday communication. Keywords: Affixes, English, Affixation process